PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL DAN MENENGAH PADA CV. MEILIAN LANCAR MAKMUR - Rompas, Debora; Morasa, Jenny; Tangkuman, Steven J. (Universitas Sam Ratulangi, 2021)
Indonesia has a financial reporting standard called SAK-EMKM (Financial Accounting Standards for Micro, Small and Medium Entities) specifically for MSMEs (Micro, Small and Medium Enterprises) which can be used as a reference in preparing MSME financial reporting which takes effect from January 1, 2018. This study aims to implement the preparation of financial statements based on Financial Accounting Standards for Micro, Small and Medium Entities (SAK-EMKM) at CV. Meilian Lancar Makmur. This study uses a qualitative method with a descriptive approach. Data obtained by making observations, interviews and documentation. The results showed that CV. Meilian Lancar Makmur, financial records are still simple, only in the form of recording cash receipts, cash disbursements and totals. In addition, CV. Meilian Lancar Makmur has not prepared financial reports based on SAK-EMKM due to lack of knowledge and has no background in accounting education. In accordance with the results of research and discussion, the authors apply SAK-EMKM as a basis for preparing financial reports on CV. Meilian Lancar Makmur is in accordance with the applicable SAK-EMKM standards. The financial statements that the authors compile are the Financial Position Report, the Profit and Loss Statement, and the Notes to the Financial Statements.